In-depth study and optimization of process parameters to enhance tensile and compressive strengths of PETG in FDM technology - Rajan Kumaresan; Kumaran Kadirgama; Mahendran Samykano; Wan Sharuzi Wan Harun; Arunkumar Thirugnanasambandam; Krishnan Kanny (Journal of Materials Research and Technology)
The advent of 3D printing and additive manufacturing (AM) marked a significant milestone in prototyping. Fused Deposition Modeling (FDM), particularly with PETG (polyethylene terephthalate glycol), has gained prominence. This study investigates the mechanical properties (tensile and compressive) and structural characteristics of PETG samples printed using FDM technology by varying the infill pattern and raster angle and reducing the infill density from 100 % to 50 %. The Response Surface Methodology (RSM) is subsequently employed to examine the experimental data and identify the parameters that substantially influence mechanical properties. According to the tensile strength testing results, the concentric pattern had the greatest values of Ultimate Tensile Strength (UTS) 25.63 MPa and Young's Modulus (E) 0.57 GPa. By conducting compression analysis, it was found that the Cubic infill pattern with 45° raster angle exhibited the maximum compressive strength of 20.00 MPa and Compressive Modulus of 2.47 GPa. This design demonstrated a superior ability to absorb compressive force when compared to the other patterns which leads to various industries such as automotive, consumer products, and biomedical devices. Additionally, the regression equations were formulated utilizing the RSM in order to optimize the attributes of the PETG material, the coefficient of determination (R2) value exceeding 75 %, indicating that they are highly suitable. The RSM clearly demonstrates that both the infill pattern and raster angle have a substantial impact on the physical properties of the FDM parts.